Nafion‐Induced Reduction of Manganese and its Impact on the Electrocatalytic Properties of a Highly Active MnFeNi Oxide for Bifunctional Oxygen Conversion. Issue 15 (16th August 2021) - Morales, Dulce M.; Villalobos, Javier; Kazakova, Mariya A.; Xiao, Jie; Risch, Marcel
Abstract: Electrocatalysts for bifunctional oxygen reduction (ORR) and oxygen evolution reactions (OER) are commonly studied under hydrodynamic conditions, rendering the use of binders necessary to ensure the mechanical stability of the electrode films. The presence of a binder, however, may influence the properties of the materials under examination to an unknown extent. Herein, we investigate the impact of Nafion on a highly active ORR/OER catalyst consisting of MnFeNi oxide nanoparticles supported on multi‐walled carbon nanotubes. Electrochemical studies revealed that, in addition to enhancing the mechanical stability and particle connectivity, Nafion poses a major impact on the ORR selectivity, which correlates with a decrease in the valence state of Mn according to X‐ray absorption spectroscopy. These findings call for awareness regarding the use of electrode additives, since in some cases the extent of their impact on the properties of electrode films cannot be regarded as negligible. Abstract : Binder's fee : The impact of Nafion on the properties of MnFeNi oxide nanoparticles as a highly active, bifunctional oxygen reduction/oxygen evolution reaction (ORR/OER) catalyst is investigated by voltammetric methods and X‐ray absorption spectroscopy. The ORR/OER activity of the catalyst increases in the presence of Nafion due to an improved particle contact, in addition to a binder‐induced Mn reduction that results in highly selective ORR sites towards the direct conversion of O2 to OH − .